Efek Pandemi Covid-19 terhadap Kinerja Keuangan dan Ekonomi Daerah Tahun 2019-2021 - Umroh, Muhammad; Utami, Finansia Palmira; Badruddin, Rudy (https://jurnal.binamandiri.ac.id/, 2023)
The Covid-19 pandemic has had an impact on various aspects of life, one of which has greatly affected the financial performance of local governments in Indonesia. The purpose of this study was to find out and test the differences in average regional financial and economic performance before and during the pandemic. Regional financial performance is measured from Regional Original Revenue and capital expenditure. The regional economy is measured by economic growth, open unemployment rate, poor population ratio, and Gini index. This research also tests the growth rate of these six variables to determine the difference in average growth in regional financial and economic performance before and during the pandemic. The sample and data for this research are 34 provinces in Indonesia for the 2019-2021 period. The analytical tools used are ANOVA analysis and the Kruskal-Wallis Test. The research results for hypothesis 1 yielded only the variables of economic growth and the open unemployment rate which showed that there was an average difference in 34 provinces in Indonesia before and during the pandemic. The results of hypothesis 2 show that there is a difference in the average growth in financial performance before and during the pandemic, while in testing the difference in the average regional economic growth that does not support the hypothesis, only the growth variable is the Gini index.